A cohesivity improver for solid waste material modification and method of use thereof, modified solid waste material
Patent Information
- Application Number
- CN202510608352.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]针对铁尾矿砂、风积沙和铅锌尾矿等小颗粒固废材料因粒径均匀且细小的特性,导致其用于路面基层材料存在的强度低等问题,本发明的目的在于提供一种用于固废材料改性的黏聚性改善剂及其使用方法、改性固废材料,通过使用黏聚性改善剂,能够显著增强固废材料之间的黏结力,改善其与其他材料的粘结能力,从而提高其在道路基层中的稳定性与压实性
1.本发明提供一种用于固废材料改性的黏聚性改善剂,通过黏土和土壤稳定剂之间的协同作用,能够显著增强固废材料之间的黏结力,改善其与其他材料的粘结能力;将固废材料作为集料用于道路基层材料中时,提高了固废材料在道路基层中的稳定性与压实性,使得固废材料的高效利用率得到了显著提升,具有重要的应用前景。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of materials engineering and environmental technology, specifically relating to a cohesive improver for modifying solid waste materials, its application method, and modified solid waste materials. Background Technology
[0002] As highway construction expands, several problems have emerged during the process. First, a large amount of excavated soil needs to be transported both internally and externally, and the cost of this disposal is constantly rising in the context of current efforts to strengthen urban environmental management. Second, semi-rigid base courses are commonly used in my country's road infrastructure, but their production and manufacturing require extensive quarrying, which not only easily leads to over-exploitation of resources but may also cause environmental problems such as soil erosion, resulting in irreversible damage to the natural ecosystem. Therefore, how to make full use of local materials and reduce the use of natural sand and gravel to lower transportation costs has become an urgent issue to be addressed in the field of road engineering.
[0003] With the increasing scarcity of natural sand resources such as quartz sand, manufactured sand, washed sand, river sand, and lake sand, we urgently need alternative materials for road base materials. The production and stockpiling of solid waste materials such as iron tailings, aeolian sand, and lead-zinc tailings have gradually expanded with the development of my country's industry. Currently, the main methods of tailings disposal are stockpiling and landfilling, which not only occupies a large amount of land resources, but also poses long-term risks to surrounding land and groundwater due to open-air tailings storage. While constructing tailings dams to store tailings, it is also necessary to prevent dam failures. The main methods of treating aeolian sand are roadbed filling and mechanical sand fixation, but these still suffer from high costs and short lifespans. These solid waste materials are all rigid substances, and their main chemical components are silicon dioxide and aluminum oxide. These chemical properties are similar to those of natural sand, thus possessing certain usability. However, while natural sand has a continuous gradation and meets engineering standards, iron tailings sand suffers from low strength and poor water stability due to particle concentration and refinement and the lack of intermediate particle sizes caused by the crushing process. Therefore, its large-scale application in road base materials is still difficult. Thus, how to rationally utilize these rigid, uniformly sized small-particle solid waste materials has become an urgent problem to be solved in the field of engineering construction. Summary of the Invention
[0004] To address the issue of low strength in road base materials due to the uniform and fine particle size of small-particle solid waste materials such as iron tailings sand, aeolian sand, and lead-zinc tailings, this invention aims to provide a cohesive modifier for modifying solid waste materials, its application method, and the modified solid waste materials. By using the cohesive modifier, the bonding force between solid waste materials can be significantly enhanced, and their adhesion to other materials can be improved, thereby increasing their stability and compaction in road base materials.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A cohesive modifier for modifying solid waste materials is provided. By weight, the raw materials comprise the following components: 50-60 parts clay, 1-5 parts soil stabilizer, and 40-50 parts water; wherein: The soil stabilizer comprises cement, lime, and composite functional additives in a mass ratio of 1:0.5-1:0.2-0.5, wherein the composite functional additives are at least one of lignin sulfonates, chitosan, and cellulose derivatives. The solid waste material is iron tailings sand, aeolian sand, or lead-zinc tailings sand.
[0006] According to the above scheme, the solid waste material is a rigid, uniformly sized small-particle solid waste material.
[0007] According to the above scheme, the particle size of the solid waste material is no greater than 4.75 mm, and the particle size is mainly concentrated in the range of 0.075-0.6 mm. Preferably, 70-90% of the particle size is concentrated in the range of 0.075-0.6 mm.
[0008] According to the above scheme, the clay is at least one of bentonite, kaolin, porcelain clay, and diatomaceous earth. Preferably, the organic matter content of the clay is no more than 5%, and the clay contains a large amount of montmorillonite, illite, and kaolinite.
[0009] According to the above scheme, the chemical composition of the solid waste material includes SiO2 and CaO, wherein by mass percentage, SiO2 is 20-60% and CaO is 10-30%.
[0010] A method for using the above-mentioned cohesive improver is provided, wherein the above-mentioned cohesive improver is added to solid waste material, stirred evenly, and then sealed for curing.
[0011] A modified solid waste material is provided, which is prepared by adding the above-mentioned cohesive improver to the solid waste material, stirring it evenly, sealing it, and then performing a curing process; wherein the solid waste material is iron tailings sand, aeolian sand, or lead-zinc tailings sand.
[0012] According to the above scheme, the mass ratio of the solid waste material to the cohesiveness improver is 7-9:1.
[0013] A road base material is provided, comprising a cementitious material and aggregates, wherein the aggregates are the aforementioned modified solid waste material.
[0014] According to the above scheme, the aggregate accounts for 80-90% of the total mass of cementitious materials and aggregates.
[0015] This invention provides a cohesive improver for modifying solid waste materials, comprising clay and a soil stabilizer. The solid waste material is a uniform small-particle material. By using clay to coat the surface of the small-particle solid waste material, the particles are effectively bonded together. Furthermore, the soil stabilizer and clay form a synergistic reinforcing network of "mineral bonding-physical filling-chemical activation" through coupling during the stabilization of the small particles. The mechanism is as follows: the nanosheets of clay (montmorillonite, kaolinite, etc.) interact with the active cations in the stabilizer (such as Ca) through surface hydroxyl groups. 2+ Al 3+ Ion exchange occurs, forming [clay-Ca-OH] composite micelles, altering their zeta potential and significantly reducing interparticle repulsion. Simultaneously, the interlayer domains of the clay can adsorb nano-CSH gels released by the stabilizer, causing the interlayer spacing of the clay to expand through the "nano-intercalation effect," forming a gradient interface transition zone that combines rigidity and toughness. This multiphase synergy improves the unconfined compressive strength of the mixture and reduces its porosity, achieving a synergistic effect of clay plasticity improvement and stabilizer cementation strengthening.
[0016] The beneficial effects of this invention are as follows: 1. This invention provides a cohesive improver for modifying solid waste materials. Through the synergistic effect between clay and soil stabilizer, it can significantly enhance the bonding force between solid waste materials and improve their adhesion to other materials. When solid waste materials are used as aggregates in road base materials, the stability and compaction of solid waste materials in road base materials are improved, and the high efficiency of solid waste material utilization is significantly enhanced, which has important application prospects.
[0017] 2. This invention provides a modified solid waste material that can be used as an aggregate to replace natural sand in combination with cementitious materials to obtain road base materials. The modified solid waste material is added in large quantities to road base materials, which not only reduces the negative environmental impact of solid waste material stockpiling, but also reduces dependence on natural sand and gravel, and lowers resource extraction and transportation costs, thus having significant environmental and economic benefits. Detailed Implementation
[0018] The technical solution of the present invention will be further explained and illustrated below through specific embodiments.
[0019] Example 1 An auxiliary cohesive improver for stabilizing iron tailings sand is provided. By weight, the raw materials include: 55 parts bentonite, 1 part cement, 0.75 parts lime, 0.25 parts hydroxypropyl methylcellulose, and 43 parts water. The iron tailings sand used has a particle size of less than 4.75 mm, with 90% of the particles concentrated in the range of 0.6-0.075 mm, a SiO2 content of 36.6%, and a CaO content of 25.9%.
[0020] A modification process for iron tailings sand is provided as follows: the above-mentioned cohesive improver is added to the iron tailings sand, the mass ratio of iron tailings sand to cohesive improver is 8:1, and after being stirred evenly, it is sealed and subjected to curing to obtain modified iron tailings sand.
[0021] A road base material is provided, comprising the following raw materials in parts by weight: 10 parts of PO 42.5 cement, 90 parts of modified iron tailings sand and water.
[0022] The maximum dry density and optimum moisture content were obtained by compaction test. At least 6 specimens were prepared by press according to the maximum dry density and optimum moisture content and then placed in a standard curing chamber (curing temperature 20±2℃, humidity 95%). After curing for 6 days, the specimens were soaked in water for 1 day, the surface moisture was wiped dry, and the unconfined compressive strength was tested according to the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering".
[0023] Example 2 Unlike Example 1, Example 2 uses 15 parts cement, 85 parts modified iron tailings, and the same amount of other raw materials. The specimens are prepared according to the preparation method in Example 1.
[0024] Comparative Example 1 Unlike Example 1, Comparative Example 1 used 10 parts cement, 90 parts unmodified iron tailings, and the same amount of other raw materials. The specimens were prepared according to the preparation method in Example 1.
[0025] Comparative Example 2 Unlike Example 1, Comparative Example 2 used 15 parts cement, 85 parts unmodified iron tailings, and the same amount of other raw materials. The specimens were prepared according to the preparation method in Example 1.
[0026] The results of Examples 1-2 and Comparative Examples 1-2 are shown in Table 1: Table 1:
[0027] Example 3 A cohesive improver for stabilizing aeolian sand is provided. The raw materials, by weight, include: 55 parts bentonite, 1 part cement, 0.75 parts lime, 0.25 parts hydroxypropyl methylcellulose, and 43 parts water. The aeolian sand used has a particle size of less than 2.36 mm, with 80% of the particles concentrated in the range of 0.3-0.075 mm, a SiO2 content of 46.6%, and a CaO content of 15.9%.
[0028] A modification process for aeolian sand is provided as follows: the above-mentioned cohesive improver is added to the aeolian sand, the mass ratio of aeolian sand to cohesive improver is 8:1, and after being stirred evenly, it is sealed and subjected to curing to obtain modified iron tailings sand.
[0029] A road base material is provided, comprising the following raw materials in parts by weight: 10 parts of PO 42.5 cement, 90 parts of modified aeolian sand, and water.
[0030] The maximum dry density and optimum moisture content were obtained by compaction test. At least 6 specimens were prepared by press according to the maximum dry density and optimum moisture content and then placed in a standard curing chamber (curing temperature 20±2℃, humidity 95%). After curing for 6 days, the specimens were soaked in water for 1 day, the surface moisture was wiped dry, and the unconfined compressive strength was tested according to the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering".
[0031] Example 4 Unlike Example 3, Example 4 uses 15 parts cement, 85 parts modified aeolian sand, and the same amount of other raw materials. The specimens are prepared according to the preparation method in Example 3.
[0032] Comparative Example 3 Unlike Example 3, Comparative Example 3 used 10 parts cement, 90 parts unmodified aeolian sand, and the same amount of other raw materials. The specimens were prepared according to the preparation method in Example 3.
[0033] Comparative Example 4 Unlike Example 3, Comparative Example 4 used 15 parts cement, 85 parts unmodified aeolian sand, and the same amount of other raw materials. The specimens were prepared according to the preparation method in Example 3.
[0034] The results of Examples 3-4 and Comparative Examples 3-4 are shown in Table 2: Table 2:
[0035] Example 5 An auxiliary cohesive improver for stabilizing lead-zinc tailings is provided. By weight, the raw materials include: 55 parts bentonite, 1 part cement, 0.75 parts lime, 0.25 parts hydroxypropyl methylcellulose, and 43 parts water. The lead-zinc tailings used have a particle size of less than 2.36 mm, with 80% of the particles concentrated in the range of 0.6-0.075 mm, a SiO2 content of 52.3%, and a CaO content of 18.4%.
[0036] A modification process for lead-zinc tailings is provided as follows: the above-mentioned cohesive improver is added to the lead-zinc tailings, the mass ratio of lead-zinc tailings to cohesive improver is 8:1, and after being stirred evenly, the mixture is sealed and subjected to curing to obtain modified iron tailings sand.
[0037] A road base material is provided, comprising the following raw materials in parts by weight: 10 parts of PO 42.5 cement, 90 parts of modified lead-zinc tailings, and water.
[0038] The maximum dry density and optimum moisture content were obtained by compaction test. At least 6 specimens were prepared by press according to the maximum dry density and optimum moisture content and then placed in a standard curing chamber (curing temperature 20±2℃, humidity 95%). After curing for 6 days, the specimens were soaked in water for 1 day, the surface moisture was wiped dry, and the unconfined compressive strength was tested according to the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering".
[0039] Example 6 Unlike Example 5, Example 6 uses 15 parts cement, 85 parts modified lead-zinc tailings, and the same amount of other raw materials. The specimens are prepared according to the preparation method in Example 5.
[0040] Comparative Example 5 Unlike Example 5, Comparative Example 5 used 10 parts cement, 90 parts unmodified lead-zinc tailings, and the same amount of other raw materials. The specimens were prepared according to the preparation method in Example 5.
[0041] Comparative Example 6 Unlike Example 5, Comparative Example 6 used 15 parts cement, 85 parts unmodified lead-zinc tailings, and the same amount of other raw materials. The specimens were prepared according to the preparation method in Example 5.
[0042] The results of Examples 5-6 and Comparative Examples 5-6 are shown in Table 3: Table 3:
[0043] As can be seen from Table 1-3: Regardless of whether it's iron tailings sand, aeolian sand, or lead-zinc tailings, the 7-day unconfined compressive strength of small-particle solid waste materials treated with cohesive improvers is significantly higher than that of untreated small-particle materials. This indicates that the interaction force between the mixture particles is significantly enhanced under the action of the cohesive improver. By utilizing the nanosheets of clay to conduct ion exchange with the active cations in the stabilizer through surface hydroxyl groups, the repulsive force between particles is significantly reduced. At the same time, the interlayer domains of clay can adsorb the nano-CSH gel released by the stabilizer, thereby effectively improving the cohesiveness of the overall material and further enhancing the overall antifreeze and erosion resistance of the material. This enables the synergistic effect of clay particles and soil stabilizers to improve the feasibility of applying small-particle materials, including small-particle solid waste materials, in road base courses.
[0044] The disclosed embodiments and the foregoing description enable those skilled in the art to implement or use the present invention. Various modifications to the embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Parts not described in detail herein are prior art and will not be elaborated upon here. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and features disclosed herein.
Claims
1. A cohesive modifier for modifying solid waste materials, characterized in that, By weight, the raw materials consist of the following components: 50-60 parts clay, 1-5 parts soil stabilizer, and 40-50 parts water; wherein: The soil stabilizer comprises cement, lime, and composite functional additives in a mass ratio of 1:0.5-1:0.2-0.5, wherein the composite functional additives are at least one of lignin sulfonates, chitosan, and cellulose derivatives. The solid waste material is iron tailings sand, aeolian sand, or lead-zinc tailings sand.
2. The cohesive improver according to claim 1, characterized in that, The solid waste material has a particle size of no more than 4.75 mm, and 70-90% of the particles are concentrated in the range of 0.075-0.6 mm.
3. The cohesive improver according to claim 1, characterized in that, The clay is at least one of bentonite, kaolin, porcelain clay, and diatomaceous earth.
4. The cohesive improver according to claim 1, characterized in that, In the solid waste material, SiO2 is 20-60 wt% and CaO is 10-30 wt%.
5. A method of using the cohesive improver according to any one of claims 1-4, characterized in that, Add the cohesive improver according to any one of claims 1-4 to the solid waste material, stir evenly, seal, and then perform a curing process.
6. A modified solid waste material, characterized in that, The solid waste material is prepared by adding the cohesive improver according to any one of claims 1-4 to the solid waste material, stirring it evenly, sealing it, and then sealing it. The solid waste material is iron tailings sand, aeolian sand, or lead-zinc tailings sand.
7. The modified solid waste material according to claim 6, characterized in that, The mass ratio of the solid waste material to the cohesive modifier is 7-9:
1.
8. A road base material, comprising cementitious materials and aggregates, characterized in that, The aggregate is the modified solid waste material as described in claim 6.
9. The road base material according to claim 8, characterized in that, The modified solid waste materials account for 80-90% of the total mass of cementitious materials and modified solid waste materials.